Tacitus and Bracciolini. The Annals Forged in the XVth Century - Ross, John Wilson, 1818-1887 (Salt Lake City, UT : Project Gutenberg, 2005)
"Tacitus and Bracciolini. The Annals Forged in the XVth Century" by John Wilson Ross is a historical account published in the late 19th century. The book focuses on the controversial claims regarding the authorship of the "Annals" attributed to Tacitus, suggesting that they were actually written by the Florentine humanist Poggio Bracciolini during the Renaissance. Ross aims to substantiate his theory through a detailed analysis of contradictions and inconsistencies within the text, as well as the historical context surrounding its emergence. The opening of the book introduces readers to Ross's central argument that the works attributed to Tacitus may have been forged as part of a deceptive literary tradition. He outlines his investigation into the authorship of the "Annals," emphasizing the moral implications of accusing a renowned historical figure of dishonesty. Ross provides critical observations about the nature of the narrative, the chronological inconsistencies, and a lack of references to the "Annals" in historical records prior to the fifteenth century. He demonstrates that significant elements in the text contradict the established understanding of ancient Roman history and sets the stage for a methodical examination aimed at proving the work's authenticity is suspect, thus engaging readers in a compelling discourse about the nature of historical integrity and authorship. (This is an automatically generated summary.)
Release date is 2005-10-01
Produced by the PG Online Distributed Proofreaders
Keywords: Tacitus, Cornelius. Annales; Bracciolini, Poggio, 1380-1459; Literary forgeries and mystifications -- History -- To 1500; Rome -- History -- Julio-Claudians, 30 B.C.-68 A.D. -- Historiography